2017
DOI: 10.1097/md.0000000000005637
|View full text |Cite
|
Sign up to set email alerts
|

Roles of real-time three-dimensional transesophageal echocardiography in peri-operation of transcatheter left atrial appendage closure

Abstract: Left atrial appendage (LAA) closure is a new treatment option for the prevention of stroke in patients with nonvalvular atrial fibrillation (AF). Conventional 2-dimensional transesophageal echocardiography (2D TEE) has some limitations in the imaging assessment of LAA closure. Real-time 3-dimensional transesophageal echocardiography (RT-3D TEE) allows for detailed morphologic assessment of the LAA. In this study, we aim to determine the clinical values of RT-3D TEE in the periprocedure of LAA closure.Thirty-ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…Co-axiality is also critical to adjust the device's angle and direction. Previous studies have demonstrated that a full view of the atrial septum can be easily obtained by RT-3D TEE, which facilitates the determination of the optimal puncture site (10,12,13). With the guidance of RT-3D TEE, no inappropriate puncture, puncture-related complications or undesirable co-axiality occurred in the present study.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Co-axiality is also critical to adjust the device's angle and direction. Previous studies have demonstrated that a full view of the atrial septum can be easily obtained by RT-3D TEE, which facilitates the determination of the optimal puncture site (10,12,13). With the guidance of RT-3D TEE, no inappropriate puncture, puncture-related complications or undesirable co-axiality occurred in the present study.…”
Section: Discussionsupporting
confidence: 55%
“…However, device sizing parameters evaluated by 2D-TEE or LAA contrast angiography were slightly smaller than the size of the implanted device. Previously, Zhou et al (12) investigated the clinical value of 3D TEE in the periprocedure of LAA closure using LeFort or LAmbre devices, both of which are locally developed devices and available in China. In accordance with the present findings, the landing zone measured by RT-3D TEE Flexi Slice mode was strongly correlated with the size of the closure device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18) Until now, clinical data on LAmbre device use is rare. 19,20) In the present study, we reported the feasibility and safety of LAAC with LAmbre in the presence or absence of prior CA procedures.…”
mentioning
confidence: 87%
“…RT-3D-TEE was used for preoperative evaluation and intraoperative monitoring in this study. Several studies have found that the accuracy of 3D-TEE was higher than that of 2D-TEE in pre-LAAC evaluation [14,15], and that 3D-TEE was highly correlated with measurements by intraoperative angiocardiography, therefore can be routinely used for intraoperative monitoring of LAAC [16]. In this study, we found correlation between the inner diameters of LAA ostium measured in 0°, 90° and 135° section by preoperative TEE and the maximum diameter measured by angiocardiography (P < 0.05), and the TEE measurement in 135° section was closest to the angiocardiography measurement.…”
Section: Discussionmentioning
confidence: 99%